Pembelajaran Kitab Al-Akhlak Lil Banat Dalam Pembentukan Karakter Santri - Khofifah, Fajriyati; Maulana, Mahrur Adam; Khasanah, Nginayatul (IAINU Kebumen, 2022)
Abstract The purpose of this study is to analyze the learning of the book of Al-Akhlak Lil Banat and the formation of the character of students in an Nahdlah Islamic boarding school. This research uses a qualitative approach. This research was conducted in an Nahdlah Islamic boarding school. The subjects of this research are the caretakers of the boarding school, the ustadz and the students. Data collection techniques using observation methods, interview methods and documentation methods. The data analysis technique used 3 techniques, namely data reduction, data display and conclusion drawing. Conclusion Learning the book of AL-Akhlak Lil Banat at the AN-Nahdlah Student Islamic Boarding School is held every Monday night or Tuesday night at the IAINU Kebumen Mosque from 19:30 to 21:00. In this learning activity, 60 students participated. Lil Banat's AL-Akhlak learning was taught by Ustadz Badrussalim, S.Pd. by using several strategies and methods used in learning. The religious character possessed by An-Nahdlah's students is good and has increased by 85%, as evidenced by the improvement in the quality of students' worship in carrying out congregational prayers, reading the Koran, and carrying out other sunnah worship. The quality of ghoiru mahdah worship also increases, the formation of the character of students who are harmonious, disciplined, mutual respect, mutual cooperation, cooperation and tawadhu. The formation of the character of students is carried out through several stages. In order to form a religious character, there are 3 efforts that we must do, namely, Uswah Hasanah, (good example, good model), habituation of habitual action (can be because it is normal) and discipline of course. Keywords: Learning, Character Education, Religion and Islamic Boarding School